(untitled) (Tribhuvan University Law Journal, 2025)
The legal system is an important part of a state. It is impossible for the state to administer justice effectively without a well-organized legal system. The administration of justice in a legal system is run and administered by the interaction of some essential organs, such as the judiciary, judges, lawyers, and law officers. There is various legal system exist throughout the world. Some of them are: Common Law; Civil/ Continental Legal System; Socialist Legal System and Hindu Legal System. The study of different legal systems revives the study of general jurisprudence from a global perspective which enables justice systems in every country to attempt to perfect their own legal system and helps in shaping foreign policies in different countries and aids in streamlining global business. The 21st century is an era where people are closer to each other and at the same time share many problems and are continuously striving against them. So to meet such challenges relating to legal systems comparative method of approach to be taken as it gives the perspective of continuous law reform. And it acts as an aid to systematic unification and harmonization of law. This article aims to give conceptual aspects of major legal system and their influence on Nepalese Legal System. The information of the article is collected from secondary authority as well as primary authority.